Exercise and Prediabetes After Renal Transplantation (EXPRED-I): A Prospective Study - Raúl Morales Febles; Domingo Marrero Miranda; Alejandro Jiménez Sosa; Ana González Rinne; Coriolano Cruz Perera; Ana Elena Rodríguez-Rodríguez; Alejandra Álvarez González; Laura Díaz Martín; Natalia Negrín Mena; Cristian Acosta Sørensen; Lourdes Pérez Tamajón; Aurelio Rodríguez Hernández; et al. (SpringerOpen, 2023)
Abstract Background Post-transplant diabetes mellitus (PTDM) beyond 12 months (late PTDM) is a severe complication after renal transplantation. Late PTDM develops mostly in subjects with prediabetes. Although exercise may have a potential role in preventing late PTDM, there are no previous data on the effect of exercise in patients with prediabetes. Material and Methods The design was a 12-month exploratory study to test the capacity of exercise in reverting prediabetes in order to prevent late-PTDM. The outcome was the reversibility of prediabetes, assessed every 3 months with oral glucose tolerance tests (OGTT). The protocol included an incremental plan of aerobic and/or strength training as well as an active plan for promoting adherence (telephone calls, digital technology, and visits). A priori, a sample size cannot be calculated which makes this an exploratory analysis. Based on previous studies, the spontaneous reversibility of prediabetes was 30% and the reversibility induced by exercise will account for another 30%, a total reversibility of 60% (p value < 0.05, assuming a potency of 85%). Ad interim analysis was performed during follow-up to test the certainty of this sample calculation. Patients beyond 12 months after renal transplantation with prediabetes were included. Results The study was interrupted early due to efficacy after the evaluation of the follow-up of 27 patients. At the end of follow-up, 16 (60%) patients reverted to normal glucose levels at fasting (from 102.13 mg/dL ± 11 to 86.75 ± 6.9, p = 0.006) and at 120 min after the OGTTs (154.44 mg/dL ± 30 to 113.0 ± 13.1, p = 0.002) and 11 patients had persistent prediabetes (40%). Also, insulin sensitivity improved with the reversibility of prediabetes, compared to those with persistent prediabetes: 0.09 [0.08-0.11] versus 0.04 [0.01-0.07], p = 0.001 (Stumvoll index). Most needed at least one increment in the prescription of exercise and compliance. Finally, measures aimed at the improvement of compliance were successful in 22 (80%) patients. Conclusion Exercise training was effective to improve glucose metabolism in renal transplant patients with prediabetes. Exercise prescription must be conducted considering both the clinical characteristics of the patients and pre-defined strategy to promote adherence. The trial registration number of the study was NCT04489043.